Iowa Birdline update, October 5, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for October 5, 1992. Highlights of the update include sightings of a first year Sabine's Gull and a late Magnolia Warbler. Also included are handwritten notes for the next week's update with sightings of nine shorebird species, such as a Sanderling, Long-billed Dowitcher and a Merlin. Epson - sheet feed/flatbed